Engineering of nun of Surat Al – Rahman the sound of ‘nun’as a model - Abbas Abdulzahra Al- Saedl, Ghassan; Majld Bachay Al- Behadily, Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
The emergence of the audio lesson among the Arabs is one of the Muslim women in the linguistic history of the Arabs that since the dawn of Islam and the descent of the Noble Qur’an, Muslims have taken to reading and reciting it as well as preserving it from distortion, so they took to memorizing it in their chests. goal in mind and then described the rules to study Arabic They described the exits of sounds and a description of "accurate" and spoke about the qualities of sounds to produce (Tajweed science). This principle was the cause of the most prominent interest of Arab scholars in the study of sounds; they make books and workbooks. Perhaps the connection of phonology with the Noble Qur’an, especially its intonation and recitation, which is based on the correct pronunciation of the sounds and controlling their exits and qualities, is what leads to saying that phonology has been linked to the science of intonation.